2011
DOI: 10.1007/s13224-011-0015-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between epidural and IV tramadol for painless labor and effect on perinatal outcome

Abstract: Objectives: To compare the efficacy of epidural and I/V Tramadol for painless labor and effect on perinatal outcome. Material and methods: A total of 90 parturients admitted in S.N. Medical College, Agra were selected for study. Thirty parturients received intravenous tramadol, thirty received epidural tramadol and thirty were kept as controls by the method of randomization. In the intravenous group, tramadol in doses of 1mg/Kg body weight IV bolus and 100mg in 500ml Ringer lactate at the rate of 8-24 drops/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 2 publications
4
13
0
Order By: Relevance
“…Moreover, in a study conducted by Jaitley et al [12] comparing epidural and IV tramadol, they reported that epidural tramadol group has an onset of analgesia with a mean (10.83 ± 4.346) min and duration of analgesia with a mean (3.77 ± 0.573) h. This was consistent with our study. Imani et al [10] concluded that epidural anesthesia with tramadol adding to lidocaine in a patient scheduled for cesarean section has a rapid onset of sensory and motor blockade and delayed request of analgesia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in a study conducted by Jaitley et al [12] comparing epidural and IV tramadol, they reported that epidural tramadol group has an onset of analgesia with a mean (10.83 ± 4.346) min and duration of analgesia with a mean (3.77 ± 0.573) h. This was consistent with our study. Imani et al [10] concluded that epidural anesthesia with tramadol adding to lidocaine in a patient scheduled for cesarean section has a rapid onset of sensory and motor blockade and delayed request of analgesia.…”
Section: Discussionsupporting
confidence: 92%
“…Calculation of sample size based upon the results of previous trial [12] revealed that at least 21 patients were required in each group to detect a significant change of the onset of sensory block of 5 minutes at alpha value of 0.05 and 95% power of study. Thirty patients were included in each group to overcome the possibility of dropout cases.…”
Section: Sample Sizementioning
confidence: 99%
“…Similar results were obtained by others as well. 6,13 The overall patient satisfaction score was significantly higher in the epidural group compared to the tramadol group, which also corroborates with a previous study. 6 The total duration of labour in the tramadol group was 489.00 min and in epidural group was 493.75 min.…”
Section: Discussionsupporting
confidence: 89%
“…Thus the difference in degree of analgesia in the two groups was statistically significant. These results were similar to Jaitley et al [16]. There is significant prolongation of the 2nd stage of labor in the epidural group (73 ± 42) min.…”
Section: Mode Of Deliverysupporting
confidence: 91%